Creating alignment echoes using a phase-shaped femtosecond laser pulse. (3rd August 2022) - Xu, Shuwu; Liu, Guizhen; Huang, Yunxia
Abstract: In recent years, molecular alignment echoes induced by a pair of time-delayed femtosecond laser pulses have been proposed and have aroused wide research interest. However, we demonstrate that an alignment echo can be alternatively produced by a shaped femtosecond laser pulse with a V-style spectral phase modulation. The full, fractional, and imaginary alignment echoes are formed by the excitation of the tailored two time-delayed sub-pulses. Both the delay time and the ratio of intensity between the two sub-pulses can be easily manipulated by designing the modulation parameters to induce various types of echoes. We further show that the optimal ratio of intensity between the two sub-pulses, which results in the maximal alignment degrees of the full echo, closely correlates with the energy of the sub-pulse. When the pulse energy is relatively low, the maximal alignment degree of the full echo is obtained when the two sub-pulses have equal intensity. The optimal ratio of intensity increases with the excitation energy of the first pump pulse.